Anatomical and Functional Outcomes of Repeat Vitrectomy Combined with Encircling Scleral Buckling for First Recurrent Rhegmatogenous Retinal Detachment After Primary Vitrectomy: A Retrospective Cohort Study - Georgios D. Panos; Alex Stubbing-Moore; Dharmalingam Kumudhan; Gavin Orr; Anwar Zaman; Craig Wilde (Journal of Clinical Medicine, 2026)
Purpose: The purpose of this study is to evaluate anatomical, visual, and safety outcomes after repeat pars plana vitrectomy combined with 360° encircling scleral buckling for first recurrent rhegmatogenous retinal detachment following primary vitrectomy. Methods: This retrospective single-centre cohort included 47 eyes of 47 patients treated between October 2016 and October 2023. The primary outcome was freedom from any subsequent retinal re-detachment during available follow-up. Secondary outcomes included final best-corrected visual acuity, timing, and management of further re-detachment, silicone oil management, and postoperative complications. Exploratory analyses described break location and final visual outcomes according to selected clinical characteristics. Results: The median age was 57.6 years, and the median follow-up was 13 months. Freedom from any subsequent retinal re-detachment was achieved in 41/47 eyes (87.2%; 95% CI 74.8–94.0%). The median final visual acuity was 0.48 logMAR. Six eyes developed a subsequent re-detachment; four required further vitrectomy with retinectomy. Among 18 break-related first recurrences, 12 involved an inferior, inferonasal, or inferotemporal break, and no subsequent re-detachment was documented in these 12 eyes during available follow-up. Clinically relevant complications occurred in 11 eyes, including treated intraocular pressure elevation in seven and buckle exposure in four. Conclusions: Repeat vitrectomy with encircling scleral buckling was followed by freedom from subsequent retinal re-detachment in 87.2% of eyes. The descriptive break location findings identify inferior break-related recurrence as a candidate phenotype for future comparative evaluation, but the absence of a repeat PPV-only comparator precludes attribution of incremental benefit to the buckle.